Nauczanie zdalne a kształcenie przyszłych pedagogów specjalnych - Głowacka, Kamila; Guzik, Julia (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
The purpose of this article was to focus on the impact of distance learning in educating future special educators. The research presented here is inconclusive as to whether distance or stationary learning is a better, more beneficial form of education. Everything depends on the lecturers, the way they convey their knowledge, as well as on the individual expectations, needs and skills of a given person.